Ethics and hermeneutics - Reyes, Ramon C. (Philippine Studies, 1987)
As a branch of philosophy, ethics may be defined as the study ofor the reflection on the. rightness or wrongness of human action. It is a fact of life that we distinguish between right and wrong actions. Very early in life, we are made to realize that not all actions are permissible. Some actions are considered praiseworthy. Others are condemned and prohibited. As we grow older we are made to appreciate the finer distinction underlying the difference between judgments regarding the feasibility or efficiency of an action, and judgments regarding the social acceptability of an action, and over and above these, judgments regarding whether an action is morally right or wrong. Mabuti bang gawain o di kaya'y masama? In ,other words, we learn to make technical judgments, socially prudential judgments and moral judgments. Thus, for example, in such an undertaking as the Chico River Dam project, it is one question to ask whether the project is technically recommendable in terms, for example, of the irrigational benefits and cheap energy it could generate. It is another question to ask whether the project is socially acceptable or politically expedient. And it is still another question to consider whether such a project is morally justifiable.